Integration Interval Determination Algorithms for BER Minimization in UWB Transmitted Reference Pulse Cluster Systems - Jin, Li; Dong, Xiaodai; Liang, Zhonghua (IEEE transactions on wireless communications, 2010)
A recently proposed transmitted reference pulse cluster (TRPC) structure contains compactly spaced reference and data pulses, and enables a low complexity, robust and practical auto-correlation detector to be used at the receiver. Previous research indicated that the integration interval of the auto-correlation detector is critical to the performance of TRPC. Therefore, in this paper, three practical data-aided algorithms are introduced to determine the integration interval of the TRPC structure: the conventional threshold-crossing concept, the new bit error rate (BER) minimization based approach, and the new hybrid scheme that combines threshold-crossing and the BER minimization concepts. The performances of the three schemes are extensively evaluated by simulation. Results show that, the BER minimization based approach and the hybrid scheme demonstrate around 2 dB performance gain over the threshold-crossing scheme in IEEE 802.15.4a channels. Moreover, the hybrid scheme yields close performance to the BER minimization based scheme with much reduced complexity.